ПРОЄКТ «БЕЗПЕЧНЕ МІСТО» ЯК ІНСТРУМЕНТ СУЧАСНОГО ПУБЛІЧНОГО УПРАВЛІННЯ - Костянтин СПОРИШЕВ; Олександр БОНДАРЕНКО (Development Service Industry Management, 2026)
The article provides a theoretical and applied substantiation of the role and place of the "Safe City" digital platform within the public administration system, specifically as an integrated component of the mechanism for ensuring state defense capability. It analyzes its functional reorientation under martial law and identifies directions for regulatory, legal, and organizational improvements in such interaction. It is noted that modern public administration extends its influence to all spheres of social life, guided by the principles of "Good Governance" and "Smart Governance." This imparts a social and humanitarian orientation to state management, shaping a new approach to understanding self-governance that meets the criteria of efficiency, openness, accessibility, accountability, and controllability, while becoming responsive to the needs and interests of citizens.The concept of a "public administration tool" is examined, and a systematization of modern public administration tools based on various criteria is carried out. It is substantiated that the "Safe City" project serves as a highly efficient, multifunctional smart tool of public administration, integrating artificial intelligence, Big Data, and video analytics. The study proves that the project's functionality extends beyond strictly law enforcement activities to encompass social development management (monitoring the safety of the educational environment, developing a barrier-free space), as well as civil protection and environmental monitoring. Special attention is paid to the project's defense capabilities under martial law, which are realized through optimizing Situational Awareness, preventive securitization of the rear, and ensuring critical infrastructure resilience.